Iron status of pregnant women and their newborns, and the necessity of iron supplementation in infants in Eastern Turkey - Poyrazoglu, Hatice Gamze; Aygun, A. Denizmen; Ustundag, Bilal; Akarsu, Saadet; Yildirmaz, Serap (Turkish Pediatrics Assoc, 2011)
Aim: Iron deficiency anemia is the most frequent cause of nutritional anemia in the first two years of life. The aim of this study was to evaluate iron status of pregnant women and their infants in Eastern Turkey and to determine their effects on iron deficiency anemia in the first year of life. Material and Method: This study was realized on 92 pregnant women classified in four groups according to their iron status and iron prophylaxis. This study was approved by The Local Ethic Committee (Firat Universitesi Tip Fakultesi Etik Kurulu 25.03.2004, 4. Session). Pregnant women were followed from the 14(th) week of gestation and blood samples of her were got at onset and of women were olatained infants at birth and on the third month, sixth month and twelfth month of life. Total blood count, serum ferritin and iron levels and total iron-binding capacity were evaluated. One way analysis of variance (ANOVA) and Pearson's and Spearman's rank test were used for statistical methods. Results: At birth, serum iron and ferritin levels were not significantly different between the four groups (p<0.05). At the third month of life; serum iron levels were diminished according to the physiologic changes and at the sixth month of life; iron deficiency anemia developed in 40% of the first group, in 57.1% of the second group, in 50% of the third group and in 69.2% of the fourth group. Conclusions: Iron status of infants is not defined only by iron stores at birth, the nutrition during the first year of life is also effective. In this study, iron deficiency anemia developed in approximately 50% of infants at the sixth month of life; despite the iron storage was sufficient at birth. Supplementation of iron in infants living in Eastern Turkey is necessary from the third month of life. (Turk Arch Ped 2011; 46: 246-51)
Do?u anadolu bölgesinde gebelerde ve do?an bebeklerinde demir durumu ve süt çocuklarında demir deste?i gereklili?i
Keywords: Infant; iron deficiency anemia; iron status; iron supplementation; pregnant woman